YOUTUBE AS AN ALTERNATIVE MEDIUM FOR APPRECIATING INDEPENDENT SHORT FILMS - Sekarnegara, Zafira Saraswati Yasmin; Handriyotopo, Handriyotopo (Seni Media Rekam ISI Surakarta, 2022)
The Covid-19 pandemic has forced people to use Youtube social media when enjoying entertainment, especially films, including independent short films. This study seeks to illustrate YouTube as an alternative medium for appreciating independent short films, particularly in Surakarta City. This study employs a qualitative research method that emphasizes a thorough and critical point of view and is supported by a phenomenological perspective. Data were collected through observation and literature study and analyzed qualitatively. The research results consider using YouTube as an alternative media for appreciating independent short films suboptimal. Most filmmakers, communities, or production houses use streaming platforms like YouTube only to promote their continued existence and create networks between filmmakers.